A scalable model for EPA and fatty acid production by Phaeodactylum tricornutum - Gu, Wenjia; Kavanagh, John M.; McClure, Dale D. (Frontiers in Bioengineering and Biotechnology, 2022)
Large-scale photoautotrophic production of microalgae has the potential to provide a sustainable supply of omega-3 fatty acids (EPA and DHA) for human and animal nutrition. This study presents a kinetic model for the EPA-producing microalga Phaeodactylum tricornutum in photoautotrophic conditions, with light and nitrogen being the growth limiting factors. The model was developed using a dataset obtained from bench-scale (5 L) cultures and was successfully validated against pilot-scale (50 L) cultures. This model is the first to predict the biomass and total fatty acid accumulation along with the EPA concentrations in the biomass and total fatty acid fraction for microalgae. The model was used to develop an optimised repeated-batch strategy; implementation of this led to increases in the biomass and EPA productivities of 50% and 20% respectively. This clearly indicates the potential of the model to be used as a tool in the design, optimisation and scale-up of microalgal systems for EPA production.